Novel technique to produce porous thermochromic VO2 nanoparticle films using gas aggregation source - Jan Prokeš; Tereza Košutová; Jaroslav Kousal; Anna Kuzminova; Ondřej Kylián (Scientific Reports)
Abstract Vanadium dioxide (VO2) is a phase transition material that undergoes semiconductor-to-metal transition at the temperature of about 68 °C. This extraordinary feature triggered intensive research focused on the controlled synthesis of VO2. In this study, we introduce and investigate an original linker- and solvent-free strategy enabling the production of highly porous VO2 nanoparticle-based films. This technique combines a gas-phase synthesis of vanadium nanoparticles and their subsequent atmospheric pressure thermal oxidation. It is shown that the thermochromic behaviour of such produced nanomaterial is at the fixed oxidation temperature strongly dependent on the oxidation time. Concerning this, it was found that there exists an optimal oxidation time (60 s in our study) that assures the production of crystalline VO2 nanoparticles with the highest, reproducible and temporally stable semiconductor-to-metal transition with the resistive switching ratio close to 2 orders of magnitude and dramatic switching of optical properties in the near infra-red spectral region.